The election of Donald Trump to the presidency and the crisis of liberalism in librarianship - Sierpe, Eino (Journal of Radical Librarianship, 2017)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Confronting librarianship and its function in the structure of white supremacy and the ethno state - Sierpe, Eino (Journal of Radical Librarianship, 2019)
Rising socio-cultural and political tensions have helped increase awareness about long-standing structures of violence and abuse, as we have seen in the development and tumultuous expansion of the #MeToo movement. However, other significant conditions of injustice and oppression continue without drawing attention. This seems to be the case with the library profession. Despite strong and persistent links to white supremacy and a well-established record excluding minorities from its ranks, the library profession has been remarkably successful in nurturing an unassailable public image of virtuous liberal benevolence and near mythical devotion to the highest ideals of freedom, individual rights, and democracy. Its unsurpassed ability in evading scrutiny or criticism of any serious consequence while maintaining a strong record of dedicated service to white power is all the more remarkable at a time where social media is used to amplify campaigns against injustices or organizations believed responsible for conditions of oppression. Although Critical Librarianship, or #CritLib, is beginning to question some of the doctrinal assumptions underlying the practice of librarianship, an examination of some of the mechanisms with which white supremacy has been able to build an entire system of racial protectionism as an occupational sector that intersects with areas of significant public interest is an important and timely research concern.
Citation Key Alias: lens.org/069-727-951-165-240, pop00317
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Gender distinctiveness, communicative competence, and the problem of gender judgments in computer-mediated communication - Sierpe, Eino (Computers in Human Behavior, 2005)
Despite persistent claims regarding the ability of text-based computer-mediated communication to neutralize gender identities, few researchers have worked on the problem of gender distinctiveness in textual production and interpretation, gender judgments, and more importantly, the role of gender in the process of impression formation in electronic communication. Against this background, the author addresses the theoretical aspects of gender in textual communication and places the problem of gender distinctiveness and gender judgments in CIVIC in the context of Hymes' model of communicative competence. He also isolates several variables worthy of investigation, namely, the provision of gender judgments, accuracy, and certainty. He then reconceptualizes the problem of gender distinctiveness and impression formation in CIVIC by bridging the gap between textual markedness and expectations. (C) 2003 Elsevier Ltd. All rights reserved.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/055-557-328-035-914 tex.type: [object Object]
Keywords: Communicative competence; Computer-mediated communication; Electronic communications; Formal languages; Gender judgments; Linguistics; Problem solving; Research; dept.ils; peer-reviewed

Managing the information revolution: library management, the control of prescriptive technologies, and the future of librarianship - Sierpe, Eino (Library Management, 2004)
This article seeks to promote a critical perspective on the present conceptualization of library management and the problems posed by technology. More specifically, it addresses the challenges faced by library administrators in relation to computing technologies. Through the adoption of Ursula Franklin's view of technology as “practice”, the article contrasts the practice of holistic and prescriptive technologies in library contexts. It also addresses the transformations of librarianship and the increasing adoption of prescriptive technological models. To exemplify the ongoing destruction of traditional librarianship, the three practices that comprise the fundamentals of librarianship are analyzed, namely, cataloging, collection development, and reference work. © 2004, Emerald Group Publishing Limited
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00170 tex.type: [object Object]
Keywords: Information management; Librarianship; Libraries; dept.ils